Response of pregnant beef cows to undegradable intake protein fed in excess of the degradable intake protein requirement - R.C. Cochran; H.H. Koster; E.S. Vanzant; Timothy J. Jones; K. C. Olson; Evan C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 1995)
Two concurrent experiments were conducted to evaluate the effect on performance and forage intake of increasing the supply of undegradable intake protein (UIP) to pregnant beef cows already receiving sufficient degradable intake protein (DIP) to maximize forage intake. Three supplements were fed at .34% BW/day, providing .092% B W/day of DIP (level determined in previous study to maximize forage intake) and .042, .059, and .077% BW/day of UIP (low , moderate, and high UIP, respectively) . In study 1, ad libitum tallgrassprairie forage intake was measured daily from 12/1/93 to 2/10/9 4 using 18 pregnant Angus x Hereford cows. Forage intake steadily increased throughout the study, but did not vary between supplements for the first 6 weeks. However , forage intake was less during the last 4 weeks for cows offered the moderate and high UIP supplements. In study 2, 117 pregnant Angus x Hereford cows grazing dormant bluestem range were used to determine the impact of the supplements on body weight and body condition changes. Level of UIP in the supplement exerted only minimal effects on cumulative or 28-day interval changes in body weight or condition.
Keywords: Cattlemen' s Day; 1995; Kansas Agricultural Experiment Station contribution; no. 95-357-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 727; Beef; Beef cows; Intake; Protein supplementation